Material modelling for structures subjected to impulsive loading - Cichocki, Krzysztof; Adamczyk, Robert; Ruchwa, Mariusz (Computer Assisted Methods in Engineering and Science, 2023)
The main results of numerical analyses of a possible design configuration of a submerged structure subjected to impulsive loading due to explosion, performed for various material models assumed for a plain concrete are presented and discussed. Three different models were considered - the modified Drucker-Prager plasticity model, brittle cracking model and the elastoplastic model with damage. The present study suggests problems and possible solutions to be applied into numerical analysis of such structures by means of available finite element computer codes.